2019
DOI: 10.1158/2159-8290.cd-19-0329
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypes of Proliferating Glioblastoma Cells Reside on a Single Axis of Variation

Abstract: Although tumor-propagating cells can be derived from glioblastomas (GBM) of the proneural and mesenchymal subtypes, a glioma stem-like cell (GSC) of the classic subtype has not been identifi ed. It is unclear whether mesenchymal GSCs (mGSC) and/or proneural GSCs (pGSC) alone are suffi cient to generate the heterogeneity observed in GBM. We performed single-cell/ single-nucleus RNA sequencing of 28 gliomas, and single-cell ATAC sequencing for 8 cases. We found that GBM GSCs reside on a single axis of variation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
281
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 259 publications
(305 citation statements)
references
References 32 publications
23
281
1
Order By: Relevance
“…Bulk and 10cRNA-seq samples were projected onto the first two principal components of the GBM C1 principal components analysis (3). Mouse genes were first converted into their human orthologs using the "biomaRt" package in R. Of the 714 human genes contributing to the principal components, 629 genes had mouse orthologs in our dataset that were used for the projection.…”
Section: Glioma Subtypingmentioning
confidence: 99%
See 4 more Smart Citations
“…Bulk and 10cRNA-seq samples were projected onto the first two principal components of the GBM C1 principal components analysis (3). Mouse genes were first converted into their human orthologs using the "biomaRt" package in R. Of the 714 human genes contributing to the principal components, 629 genes had mouse orthologs in our dataset that were used for the projection.…”
Section: Glioma Subtypingmentioning
confidence: 99%
“…Subsequent work at the single-cell level suggested that intratumor heterogeneity of advanced gliomas is substantial (4), with the proportion of different cell types (recruited astrocytes vs. microglia) and cell states (proneural vs. mesenchymal) dictating the bulk classification. Glioma-propagating cells are now proposed to reside on a spectrum of proneural-to-mesenchymal cell fate, which is orthogonal to a cell's proliferative state (3). The question of subtyping is also separate from differential expression, as many of the markers delineating a subtype will reflect vestiges of the cell type in which the tumor appeared.…”
Section: Lcm-based Rna Sequencing Validates Differential Gene Expressmentioning
confidence: 99%
See 3 more Smart Citations